Numerical investigation of lens based setup for depth sensitive diffuse reflectance measurements in an epithelial cancer model - Liu, Quan (2013)
Lens based setups have been explored for non-contact diffuse reflectance measurements to reduce the uncertainty due to inconsistent probe-sample pressure in the past years. However, there have been no reports describing the details of Monte Carlo modeling of lens based non-contact setup for depth sensitive diffuse reflectance measurements to the best of our knowledge. In this study, we first presented a flexible Monte Carlo method to model non-contact diffuse reflectance measurements in a lens based setup. Then this method was used to simulate diffuse reflectance measurements from a squamous cell carcinoma (SCC) tissue model in the cone shell, cone and hybrid configurations, in which the cone shell configuration has not been previously proposed in optical spectroscopy. Depth sensitive measurements were achieved by adjusting the following two parameters: (1) the depth of focal point of the imaging lens in the SCC model; and (2) the cone radius in the cone configuration or the ring radius in the cone shell configuration. It was demonstrated that the cone shell and the hybrid configurations in general have better depth sensitivity to the tumor and the stroma than the more commonly used cone configuration for diffuse reflectance measurements in the SCC model.